Genetic variants of COVID-19 and vaccination. Is there a Correlation? - Nagwa Ali Sabri; Mohamed Ahmed Raslan; Eslam Mansour Shehata; Sara Ahmed Raslan (Open Journal of Proteomics and Genomics - Peertechz Publications, 2022)
Background: New coronavirus disease is considered one of the most widely spreading viral infections all over the world. Increased numbers of severe covid-19 cases are growing up. Gene sequencing and discovering new viral variants is an essential aspect during the pandemic. The generation of treatment-resistant viral strains and the probability of negative impact on vaccination efficacy is possible. We aimed to review the probable effect of new variant emergence on treatment and vaccination efficacy, besides, the importance of gene sequencing from published literature data till the moment.  Main body of the abstract: SARS-CoV-2 genome studies indicated that it shared 79 to 82% nucleotide similarity with SARS-CoV-1. Several gene locations in the envelope (E) structural protein c.222G>C (p. Leu74Leu) and the Membrane (M) structural protein c.213C>T (p. Tyr71Tyr) were proved to have mutations. Also, the surface (S) gene mutation c.1841A>G (p. Asp614Gly) is most relevant. The published sequences in Egypt are accounting for less than 0.2 percent of reported instances.  Short conclusion: The possibility of rapid generation of treatment-resistant viral strains is highly possible. As a consequence of genetic alterations that impart functional differences in infectivity, sub-strains might arise as a result of acquired immunity that is likely to diminish over time and become less effective against increasingly aggressive strains. Gene sequencing in Egypt requires a lot of efforts to provide a rapid discovery for new emerging variants, to avoid a possible decrease in vaccination efficacy and emergence of treatment-resistant strains.